Konsep Pemberdayaan (Tamkīn) Perspektif Al-Qur’an: The Concept of Empowerment (Tamkīn) in the Perspective of the Qur'an - Ihwan Wahid Minu; Lince Bulutoding; Abdul Wahab (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This research aims to examine the term tamkīn in the Al-Qur'an, identify its categorization, and analyze its function at a practical level. This research is in the nature of a library research, namely collecting data sourced from libraries (both individual and institutional libraries), because the data studied is in the form of books, manuscripts or magazines sourced from the library treasury. The results of this research show several things. First, the term tamkīn in the Al-Qur'an has several meanings, namely the granting of power or kingdom, position at the side of the ruler, preparation for attaining power, granting worldly favors, steadfastness in religion, and stability and victory. Second, the division of tamkīn in the Al-Qur'an consists of two types, namely maddi and artiwi. tamkīn maddi relates to giving strength in the form of property, wealth, or resources to achieve economic and social independence, while tamkīn artiwi focuses more on spiritual, mental, or moral strength, which includes the quality of faith and the ability to carry out religious and social obligations. Third, the concept of tamkīn in everyday life leads to empowerment in various aspects, such as economic, social, spiritual, educational and leadership. Allah SWT. through His revelation, it provides instructions for His people to pay attention to the principles of justice, prosperity and progress.